2020
DOI: 10.1371/journal.pcbi.1007680
|View full text |Cite
|
Sign up to set email alerts
|

Performance of virtual screening against GPCR homology models: Impact of template selection and treatment of binding site plasticity

Abstract: Rational drug design for G protein-coupled receptors (GPCRs) is limited by the small number of available atomic resolution structures. We assessed the use of homology modeling to predict the structures of two therapeutically relevant GPCRs and strategies to improve the performance of virtual screening against modeled binding sites. Homology models of the D 2 dopamine (D 2 R) and serotonin 5-HT 2A receptors (5-HT 2A R) were generated based on crystal structures of 16 different GPCRs. Comparison of the homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 93 publications
0
32
1
Order By: Relevance
“…Considering that our approach is largely automated, the effort to generate and inspect additional complexes as part of lead optimization process is relatively small. Prediction accuracy could likely be further improved by using more advanced methods for selecting representative snapshots from the MD simulations [47,48] and incorporation of targetspecific knowledge regarding ligand-residue contacts, mutagenesis data, and structure-activity relationships for known ligands [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that our approach is largely automated, the effort to generate and inspect additional complexes as part of lead optimization process is relatively small. Prediction accuracy could likely be further improved by using more advanced methods for selecting representative snapshots from the MD simulations [47,48] and incorporation of targetspecific knowledge regarding ligand-residue contacts, mutagenesis data, and structure-activity relationships for known ligands [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The best benchmarked modeling pair choices, as well as pairs which did not perform well, were considered for the analysis. The performance of the templates was ranked as good or bad, in published studies, on the basis of good ligand enrichment in VLS ( Perry et al, 2015 ; Loo et al, 2018 ; Jaiteh et al, 2020 ), local and global (RMSD) from crystal structures ( Castleman et al, 2019 ), and both ligand enrichment and RMSD from the crystal structure ( Shahaf et al, 2016 ). Researchers have compared varied parameters in these studies among the target-template pairs, including global sequence identity, TM-wise sequence identity, local sequence identity (identity within the binding pocket), model refinement through molecular dynamics and/or induced-fit docking, and the ligand binding site plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Models based on local similarity measures have produced better results in virtual screening experiments ( Castleman et al, 2019 ; Szwabowski et al, 2020 ). Multiple studies have shown that sequence identity above 30% could result in good GPCR homology models (within 3 Å) ( Shahaf et al, 2016 ; Loo et al, 2018 ; Jaiteh et al, 2020 ). But most of the GPCRs share low sequence identity with available templates.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether this is really an advantage for GPCR drug discovery is a current debate. In a recent publication on the performance of virtual screening against GPCR homology models 12 , in which binding site plasticity was considered by including ensembles of structures, it was shown that MD refinement resulted in moderate improvements of structural accuracy and the virtual screening performance of snapshots was either comparable to or worse than that of the raw homology models 12 . However, and from a different perspective, the methodological approach herein shown is focused on the statistical significance of structural features reflecting receptor activation.…”
Section: Resultsmentioning
confidence: 99%